Understanding glyph characteristics on the legibility for native and non-native speakers in virtual reality - Zhang, Huidan; Sakamoto, Daisuke; Ono, Tetsuo (Frontiers in Virtual Reality, 2025)
IntroductionMultilingual communication shapes education, culture, and decision-making, However, we lack a clear picture of how native writing systems influence visual processing.MethodsWe conducted virtual reality experiments comparing native Chinese, Japanese, and English readers, who read both native and non-native scripts in immersive VR settings.ResultsNative Chinese and Japanese readers read faster but were more prone to confusion with similar glyphs, while English readers took longer and struggled with structural complexity. These patterns among native Chinese and Japanese readers persisted even with non-native scripts.DiscussionOur findings reveal a lasting visual divergence shaped by native-script experience, offering guidance for VR interface design and script-sensitive language learning tools.